ACTIVE CURATION FOR CULTURAL COMMENTARY: YOUNG ADULTS, ALGORITHMS, AND NEWS CONTENT ON SOCIAL MEDIA - Stepnik, Agata Joanna (AoIR Selected Papers of Internet Research, 2023)
As social media platforms have become a key source of news for younger generations of users (Newman et al., 2021), media plurality and news visibility have become focal areas for scholars concerned about the future of local content in an era of information globalisation (see esp. Dwyer et al., 2020) and algorithmic gatekeeping (Martin, 2021). Consequently, it is crucial to understand how young adults curate their social media feeds to access socially significant information and the impact that their curatorial design has on their news exposure and consumption. This paper presents the findings from a 12 month digital ethnographic study involving 13 young adult Australians and their use of social media platforms such as Facebook, Instagram and TikTok to highlight the role of individual agency in user experience of news and information. The findings in this paper examine what users categorise as news on social media, and explores how topics discussed in the media are able to break through onto social media feeds without presentation as formal news reporting. It argues that ‘cultural commentary’ content such as memes, casual discussions between friends, and hot takes from influencers and public figures have the potential to keep users up to date with what is happening in the world, hyper-locally and globally. The analysis of the research data demonstrates that a variety of platform users interact with cultural commentary content, including those who describe themselves as ‘news avoidant’.